The chloride anion acts as a second messenger in mammalian cells modifying the expression of specific genes - Valdivieso, Ángel Gabriel (2016)
Fil: Valdivieso, Ángel G. Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina